Does The Scheme “Free Bus Policy for Women in Public Transportation” Contributes to The Achievement of The Sustainable Development Goals? - Joel Premkumar, Jilly Philippa; M.S., Sameem Banu; J, Meenal (Indonesian Journal of Social Research (IJSR), 2023)
Tamilnadu, one of the states in India is performing better in achieving Sustainable Development Goals (SDGs) by implementing various schemes and programmes. One such scheme “Free bus travel for women in public transportation”, was launched in June 2021 in an effort to reduce the cost of travel and enhance women’s work participation rates. Women's mobility is essential for increased labour force participation, higher wages and salaries. The aim of this scheme is to help women, especially those who earn a living on a daily basis, become economically independent and free from poverty. Therefore, this study was conducted to analyse the impact of the scheme with the various relevant SDGs. It is a descriptive paper that highlights the policy’s various benefits on women, whether it contributes to the achievement of various sustainable development goals such as Goal 1.4 (access to basic services), Goal 4.3 (Equal access to tertiary education), Goal 5.2 (elimination of violence against women in public and private sphere), Goal 8.5 (decent work) & Goal 11.2 (safe public transportation) using both quantitative survey and qualitative interviews which was carried out among 150 women commuters in Sivagangai District. The scheme was shown to have a good effect on women by assisting them in meeting their practical needs, such as gaining access to markets and schools, and by assisting them in strategically empowering themselves by providing access to social and economic possibilities.